Coastal Ethnomathematics in Geometry Learning: A Study at Senior High Schools in Panimbang Regency - Y, Setyo Luthfi Okta (Research Collaboration Community (Rescollacom), 2024)
This study examines the integration of coastal ethnomathematics into geometry learning in senior high schools in Panimbang Regency, Indonesia. Ethnomathematics merges local cultural elements with mathematical concepts, providing a contextualized approach to teaching. The research focuses on how coastal culture, such as fishing boat designs and net patterns, can be used to teach geometric concepts like symmetry, angles, and shapes. A pretest-posttest experimental design was conducted with 30 Grade X students. Initially, students were taught using a traditional method, followed by a pretest to assess their understanding. They then learned geometry through coastal cultural examples, with a posttest measuring their progress. The average test score improved from 61.4 to 77.2, indicating a significant enhancement in learning outcomes. A questionnaire revealed that students found the ethnomathematics approach made geometry more relatable, easier to grasp, and increased their motivation. The study concludes that integrating ethnomathematics into geometry lessons not only improves students' understanding and engagement but also fosters a greater appreciation for their local culture